2014
DOI: 10.1186/1471-2407-14-637
|View full text |Cite
|
Sign up to set email alerts
|

Time trends of cancer incidence in Setif, Algeria, 1986–2010: an observational study

Abstract: Background: Incidence rates of various cancers are increasing in Arab countries and are expected to reach those of industrialized ones in few decades. This paper aimed to describe the incidence rates of most common cancers -and/or of those cancer preventable through modifiable behaviors -recorded in the province of Setif, Algeria from 1986 through 2010. Methods: Cancer diagnoses for the 1986-2010 period were provided by the population-based Cancer Registry of Setif, disentangled by site, morphology, age (quinq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 22 publications
4
28
4
Order By: Relevance
“…This difference in incidence is greater than those reported in previous studies among North Africans [3] and Algerian population [4]. We have also shown that cigarette smoking was a significant risk factor for bladder cancer risk (OR=3.55; CI: 2.9-5.48; p=1.21E-08).…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…This difference in incidence is greater than those reported in previous studies among North Africans [3] and Algerian population [4]. We have also shown that cigarette smoking was a significant risk factor for bladder cancer risk (OR=3.55; CI: 2.9-5.48; p=1.21E-08).…”
Section: Discussioncontrasting
confidence: 48%
“…Between 2006 and 2010, the incidence for Algerian men were 10.3/100,000 person-years, this represents 9.1% of the global cancer incidence in Algeria [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed that 60 years was the mean age at diagnosis in northern Tunisia that is slightly higher than that observed in other north-African countries such as Morocco and Algeria with an average age around 55 years [37][38][39][40]. The average age is much lower in Egypt and some African countries with, respectively, 50 and 47 years [31,[41][42][43].…”
Section: Discussionmentioning
confidence: 61%
“…8 (1993–1997) [15] and from cancer registry reports for years 2003, 2006, and 2007 [16–18]. Time trends of cancer incidence in Setif, Algeria, 1986–2010 were recently reported [19] and additional data were obtained from CIV Vol. 6 (1986–1989) [13], Vol.…”
Section: Methodsmentioning
confidence: 99%